Economics principles, problems, and policies - McConnell, Campbell R. (The McGraw-Hill series in economics, 2009)
Introduction to economics and the economy; Microeconomics of product markets; Microeconomics of resource markets; Microeconomics of Government; Microeconomic issues and policies...